Historical changes in grassland area determined the demography of semi-natural grassland butterflies in Japan - Nakahama, Naoyuki (Heredity (Edinb), 2018)
Semi-natural grassland areas expanded worldwide several thousand years ago following an increase in anthropogenic activities. However, semi-natural grassland habitat areas have been declining in recent decades due to changes in landuse, which have caused a loss of grassland biodiversity. Reconstructing historical and recent demographic changes in semi-natural grassland species will help clarify the factors affecting their population decline. Here we quantified past and recent demographic histories of Melitaea ambigua (Lepidoptera; Nymphalidae), an endangered grassland butterfly species in Japan. We examined changes in demography over the past 10,000 years based on 1378 bp of mitochondrial COI gene. We then examined changes in its genetic diversity and structure during the last 30 years using nine microsatellite DNA markers. The effective population size of M. ambigua increased about 3000–6000 years ago. In contrast, the genetic diversity and effective population sizes of many populations significantly declined from the 1980s to 2010s, which is consistent with a recent decline in the species population size. Our data suggest that the M. ambigua demography can be traced to changes in area covered by semi-natural grasslands throughout the Holocene.